strew-strewn-strewn

answers: 1

Register to add an answer

The time for answering the question is over

108 cents

Answer:

Equating the expression with 0,

2x

2

−5x+2

On factorising it further,

2x

2

−4x−x+2=0

2x(x−2)−1(x−2)=0

(2x−1)(x−2)=0

∴x=

2

1

or x=2

∴ The zeroes of 2x

2

−5x+2 are

2

1

and 2.

hope it would help you

314

Eleonora

For answers need to register.

Contacts

mail@expertinstudy.com

Feedback

Expert in study

About us

For new users

For new experts

Terms and Conditions